Redescription with new molecular data of rare genus and species Iotonchulus longicaudatus Baqri, Baqri and Jairajpuri, 1978 (Mononchida, Iotonchidae) from Vietnam - Thanh Tam, Vu Thi; Le, Thi Mai Linh (Academia Journal of Biology, 2026)
The rare genus and species Iotonchulus longicaudatus (Baqri, Baqri & Jairajpuri, 1978) Andrássy, 1993b was previously found only in India. This species was first recorded in Vietnam at the Cat Tien National Park (Ho Chi Minh City) and is currently recorded in several natural areas: Phia Oac (Cao Bang), Van Ban (Lao Cai) and Con Dao Island (Ho Chi Minh City). The new illustrations with re-description and new molecular data were presented.